2017
DOI: 10.1007/s12022-017-9476-5
|View full text |Cite
|
Sign up to set email alerts
|

The Flip Side of NIFTP: an Increase in Rates of Unfavorable Histologic Parameters in the Remainder of Papillary Thyroid Carcinomas

Abstract: The term noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) was recently proposed to replace noninvasive follicular variant of papillary thyroid carcinoma (FVPTC) both to promote more conservative management of these tumors and spare patients the psychological burden of a cancer diagnosis. This reclassification will lower the incidence of papillary thyroid carcinoma (PTC). In addition, it could result in an increase in the rates of unfavorable histologic prognosticators for PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Specifically, features such as >1% true papillae formation, psammoma bodies, and the focal presence of other variants of PTC (eg, >30% solid, trabecular, or insular growth pattern) may have been overlooked in cases previously diagnosed as noninvasive encapsulated FVPTC before NIFTP inception. A recent study by Wong et al has shown that the delineation of NIFTP criteria has increased the rates of unfavorable histologic parameters in PTCs that do not qualify as NIFTP . Moreover, a few implicit criteria regarding NIFTP are worth mentioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, features such as >1% true papillae formation, psammoma bodies, and the focal presence of other variants of PTC (eg, >30% solid, trabecular, or insular growth pattern) may have been overlooked in cases previously diagnosed as noninvasive encapsulated FVPTC before NIFTP inception. A recent study by Wong et al has shown that the delineation of NIFTP criteria has increased the rates of unfavorable histologic parameters in PTCs that do not qualify as NIFTP . Moreover, a few implicit criteria regarding NIFTP are worth mentioning.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wong et al has shown that the delineation of NIFTP criteria has increased the rates of unfavorable histologic parameters in PTCs that do not qualify as NIFTP. 24 Moreover, a few implicit criteria regarding NIFTP are worth mentioning. First, oncocytic neoplasms were not included in the original NIFTP report and therefore were not part of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The predictions, which were based on retrospective data from four institutions (three Italian and one American), resulted in a calculated rate of NIFTP of 18.6% among all PTC cases (4). After more than 3 years from the introduction of the new nomenclature, it appears that the initial calculations were overestimated (8,9,10,11,12,13,14,15,16,17,18,19,20,21).…”
Section: Epidemiologymentioning
confidence: 99%
“…Additionally, in our study lymph node metastases were present in only two cases; one case had a PTC with tall cell features and both cases had multifocal microcarcinomas. Although examination of the negative histological features associated with PTCs was beyond the scope of our study, Wong et al noted that in reclassifying NIFTPs as benign neoplasms, the rates of unfavourable parameters such as extrathyroidal extension, lymphovascular invasion and lymph node metastases increased in the other subtypes of PTCs. More studies with long‐term follow‐up will be needed to fully characterise the prognostic implications of this diagnostic paradigm shift on other PTCs.…”
Section: Discussionmentioning
confidence: 99%